Two RhIII-substituted polyoxoniobates and their base-induced transformation: [H2RhNb9O28]6− and [Rh2(OH)4Nb10O30]8−. Issue 47 (16th November 2015) - Son, Jung-Ho; Casey, Willam H.
Abstract : Two new rhodium-substituted polyoxoniobates, [H2 RhNb9 O28 ] 6− (RhNb9 ) and [Rh2 (OH)4 Nb10 O30 ] 8− (Rh2 Nb10 ) are reported. Abstract : Two new rhodium-substituted polyoxoniobates, [H2 RhNb9 O28 ] 6− (RhNb9 ) and [Rh2 (OH)4 Nb10 O30 ] 8− (Rh2 Nb10 ) are reported. The two distinct Rh III -substituted niobate clusters behave differently when the pH is raised with TMAOH: the Rh2 Nb10 is stable until pH ∼ 12.7, but RhNb9 dissociates to form RhNb5 and RhNb10, similar to some of our other metal-substituted niobates, such as the MNb9 ions (M = Cr or Mn), which transform to MNb10 when the solution pH is raised.